Kekerasan Permukaan Restorasi Seramik dan Pengunyahan - Sastrodihardjo, Sumadhi (Jurnal Material Kedokteran Gigi, 2023)
The most important criteria for dental materials is durability and compatibility with opposing structures in using. Ceramics is used in making restoration due to obtain the estretic factor. There are several restorations obtained by using ceramics such as all porcelain crown, porcelain fused to metal, ceramic inlay, onlay dan veneers. Ceramics have brittle properties but however they have a good surface hardness properties. Ceramic restoration face the antagonist tooth or other restoration in the oral cavity during mastication. Higher surface hardness of ceramic restoration than the hardness of teeth or restoration materials causing wear of teeth or other materials used. Otherwise the lower surface hardness of ceramic will cause damage on ceramic restoration due to its brittle properties. In this paper the result of researchs related to the surface hardness of ceramics is also presented.